The 2013 Curriculum Implementation Review The Pedagogical Competence And Mastery Of Information And Communication Technology Teachers At SD Negeri - Dido Wendi (Pedagogi: Jurnal Ilmu Pendidikan, 2020)
This study aims to analyze the teacher's Pedagogical and technology competence in the implementation of the Curriculum 2013. The research used a descriptive qualitative approach. Implementation of the Curriculum 2013 includes dimensions of curriculum concepts, procurement of books, learning activities, and learning assessment. Implementation of the Curriculum 2013 in terms of teacher pedagogics includes nine aspects. The implementation of the Curriculum 2013 in terms of mastery of information and communication technology teachers includes 1) ICTs used, 2) Development activities of subject matter using ICTs, 3) forms of use of it. Implementation of the 2013 Curriculum accommodates student learning needs. The provision of books is following the provisions. Student learning activities are student-centered. The assessment shows an emphasis on authentic attitude and knowledge assessment. The implementation of the Curriculum 2013 in the dimension of teachers' pedagogical competence in the good category. The implementation of the 2013 curriculum in the dimensions of ICT mastery by teachers based on interview data, questionnaires, and observations is quite well categorized in terms of the technology used, the activities of using ICT, and its use as a learning medium.